Performance of Automatic Detector & Locator Tested on Synthetic Seismograms - Eva Káldy; Tomáš Fischer (Seismica)
Seismic network sensitivity and event detection performance are critical for assessing earthquake risks, particularly in regions susceptible to induced seismicity. In seismically inactive zones, the network monitoring presents unique challenges, even when adapting automated detection and location systems originally designed for active zones.